Selective oxidation of thioanisole by titanium complexes immobilized on mesoporous silica nanoparticles: elucidating the environment of titanium(iv) species. Issue 3 (8th January 2019) - Cruz, Paula; Fajardo, Mariano; del Hierro, Isabel; Pérez, Yolanda
Abstract : The coordination environment of titanium of the catalysts was investigated by DRUV–vis, Raman and 47/49 Ti MAS-NMR spectroscopies and solid-state electrochemical techniques. Abstract : Titanium-immobilized materials based on mesoporous silica nanoparticles (MSNs) were prepared via a simple one-step method with a silylating agent and titanium precursors with different electronic and sterical characteristics. The mesostructure of the materials was confirmed by X-ray diffraction and N2 adsorption–desorption isotherm studies and their nanospherical morphology demonstrated by transmission electron microscopy (TEM). The titanium materials were also characterized by X-ray fluorescence (XRF), 13 C CP/MAS NMR spectroscopy (MAS-NMR) and Fourier-transform infrared spectroscopy (FT-IR). The synthesized materials were highly efficient and recyclable catalysts for the selective oxidation of thioanisole with hydrogen peroxide, as a green oxidant, at room temperature and after 5 min of reaction time. In addition, UV–vis diffuse reflectance, Raman and 47/49 Ti MAS-NMR spectroscopies and solid-state electrochemical techniques were employed to study the titanium environment of fresh and reused catalysts.